Osteochondroma involving mandibular condyle - Latika Bachani; Ashok Lingappa; Shivaprasad Shankaramurthy; Sujatha Gulagadar Parameshwarappa (Wolters Kluwer Medknow Publications, 2017)
Osteochondroma is defined as an osteocartilagenous exostosis with cartilage capped exophytic lesion that arises from the bone cortex. It is a slow growing benign tumor that is rarely seen in the maxillofacial region. Osteochondroma of the mandibular condyle is a relatively rare condition that causes a progressive enlargement of the condyle, usually resulting in facial asymmetry, temporomandibular joint (TMJ) dysfunction and malocclusion. Radiographically, there is a unilaterally enlarged condyle usually with an exophytic growth of the tumor from the condylar head. The treatment of osteochondroma is primarily surgical resection of the tumor. This paper reports a case of osteochondroma of the right mandibular condyle presenting as a painless restricted mouth opening.